4DRadarRBD: 4D mmWave radar-based road boundary detection in autonomous driving - Wu, Yuyan; Noh, Hae Young (Frontiers in Signal Processing, 2025)
IntroductionDetecting road boundaries, the static physical edges of the available driving area, is important for safe navigation and effective path planning in autonomous driving and advanced driver-assistance systems. Traditionally, road boundary detection in autonomous driving relies on cameras and LiDAR. However, they are vulnerable to poor lighting conditions, such as nighttime and direct sunlight glare, or prohibitively expensive for low-end vehicles.MethodsThis paper introduces 4DRadarRBD, the first road boundary curve detection method based on 4D mmWave radar, which is cost-effective and robust in complex driving scenarios. The main idea is that road boundaries (e.g., fences, bushes, roadblocks) reflect millimeter waves, thus generating point cloud data for the radar. To overcome the challenge that the 4D mmWave radar point clouds contain many noisy points, we initially reduce noisy points via physical constraints for road boundaries and then segment the road boundary points from the noisy points by incorporating a distance-based loss which penalizes for falsely detecting the points far away from the actual road boundaries. In addition, we capture the temporal dynamics of point cloud sequences by utilizing each point’s deviation from the vehicle motion-compensated road boundary detection result obtained from the previous frame, along with the spatial distribution of the point cloud for point-wise road boundary segmentation.ResultsWe evaluated 4DRadarRBD through real-world driving tests and achieved a road boundary point segmentation accuracy of 93%, with a median distance error of up to 0.023 m and an error reduction of 92.6% compared to the baseline model.